Promoting the development of ethnic medicine in China: policy evaluation and optimization countermeasures - Lan, Yafei; Zhang, Junlin; Jiao, Zufang; Mao, Ningying (Frontiers in Public Health, 2024)
Background The coordinated development of ethnic medicine is a basic necessity for steady construction of a healthy China. This process includes closely following domestic and foreign policies, including changes, through the optimization of policies; shaping the new direction of the development of national medicine; and achieving comprehensive technological and industrial upgrades. As such, ensuring the all-round development of national medicine in China remains a great challenge. Methods This paper takes the relevant policies of national and local ethnic medicine issued by the government as the research object, and, through the full interpretation of the policy-issuing body, policy content, and policy effectiveness, deeply analyzes the current situation of the policy’s role in ethnic medicine and explores the distribution of policy types, subject-cooperation modes, and scoring levels in various dimensions. Results This study found that, in the new era of pharmaceutical reform, the State lacks a variety of special policies on ethnomedicine, and there is also an imbalance in the use of policy tools at both the central and local levels as well as synergies in the implementation of policies that need to be further strengthened. Discussion There remains a need to continue to improve the policy-evaluation system, optimize the structure for the use of policy tools, and improve the rates of application and implementation of the national medicine policy by strengthening cross-provincial and multisectoral cooperation to promote the revitalization of the national medicine industry in China.